2021
DOI: 10.1021/acschembio.1c00552
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulators Enhancing GLP-1 Binding to GLP-1R via a Transmembrane Site

Abstract: The glucagon-like peptide-1 receptor (GLP-1R) is a well-established drug target for the treatment of type II diabetes. The development of small-molecule positive allosteric modulators (PAMs) of GLP-1R is a promising therapeutic strategy. Here, we report the discovery and characterization of PAMs with distinct chemotypes, binding to a cryptic pocket formed by the cytoplasmic half of TM3, TM5, and TM6. Molecular dynamic simulations and mutagenesis studies indicate that the PAM enlarges the orthosteric pocket to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The in vivo response of the transfected cells with the rs10305492 polymorphism to various GLP-1 agonists (oxyntomodulin, glucagon, semaglutide, and tirzepatide) showed increased protein Gαs recruitment and GLP-1R endocytosis [41]. Moreover, this missense variant caused a loss of hydrophobic interactions and a gain of polar interactions with nearby residues (Asn320 and Gly318), part of the transmembrane binding pocket of the GLP-1R: GLP-1 complex [42]. The response on G-protein coupling capacity of different GLP1R mutation assessed in vitro was negatively correlated with participants' random glucose levels, supporting the clinical observation of lower fasting blood glucose levels in GLP1R A316T polymorphism carriers [34].…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo response of the transfected cells with the rs10305492 polymorphism to various GLP-1 agonists (oxyntomodulin, glucagon, semaglutide, and tirzepatide) showed increased protein Gαs recruitment and GLP-1R endocytosis [41]. Moreover, this missense variant caused a loss of hydrophobic interactions and a gain of polar interactions with nearby residues (Asn320 and Gly318), part of the transmembrane binding pocket of the GLP-1R: GLP-1 complex [42]. The response on G-protein coupling capacity of different GLP1R mutation assessed in vitro was negatively correlated with participants' random glucose levels, supporting the clinical observation of lower fasting blood glucose levels in GLP1R A316T polymorphism carriers [34].…”
Section: Discussionmentioning
confidence: 99%
“…Small molecular GPCR modulators, including orthosteric and allosteric ligands, still represent a significant fraction of new FDA-approved drugs . Allosteric modulators have been shown to bind at diverse GPCR sites, including in contact with the phospholipid bilayer. With the discovery of new GPCR PAMs we have begun to appreciate the range of receptor allosteric binding sites. In a search for cryptic pockets on GPCRs that do not yet have proven examples from structural studies, an exofacial site termed OS9 that is comparable to the identified A 3 AR PAM site was predicted by Hedderich et al PAMs for the A 1 AR (VCP171) and M 2 muscarinic receptor (LY2119620) dock to a site superficial to the orthosteric binding site essentially “trapping” the agonist. , Other PAMs bind intracellularly, such as to the D 1 dopamine receptor (DETQ) and β 2 adrenergic receptor (Compound 6) with the latter being shown to make key interactions with intracellular loop 2 (ICL2) stabilizing the receptor in such a way as to favor G protein binding. More recently, an A 1 AR cryo-EM structure in complex with its endogenous agonist adenosine, a newer PAM for the receptor (MIPS521), and the Gα i2 protein has been determined. , Interestingly, at the M 4 muscarinic receptor xanomeline was found to modulate at both orthosteric and allosteric sites, as is also predicted for the parent A 3 AR PAM 3 .…”
Section: Discussionmentioning
confidence: 99%
“…25 For comparison, 2-cyclopentyl-4-phenoxy-3H-imidazo-[4,5-c]quinoline (DU124182) was previously found to be moderately active as a hA 3 AR PAM. 38 Since mutation of P 7.50 within the NPxxY motif would not be tolerated for activation, 39 the corresponding ether (57) and thioether (58) derivatives of 3 at position 1 of the heterocycle were generated and found to exhibit submaximal PAM activity providing support of a H-bonding interaction. Furthermore, adding lipid chains (65,66) failed to improve the pharmacological profile.…”
Section: Strategy Leading To the Lipid Trolling Approachmentioning
confidence: 99%
“…Cryptic sites can provide unforeseen tractable drug target sites, thus expanding the druggable proteome considerably (Vajda et al ., 2018 ; Hopkins and Groom, 2002 ). On one hand, cryptic pockets offer the prospect to design allosteric drugs (Wenthur et al ., 2014 ), a strategy that could be exploited as a therapeutic path towards treating cancer (Zhong et al ., 2021 ), diabetes (Wang et al ., 2021a ), and more recently, SARS-CoV-2 infections (Zimmerman et al ., 2021 ). On the other hand, cryptic pockets commonly occur at protein–protein interfaces [PPI; (see section ‘Drugs targeting protein–protein interactions’)].…”
Section: Protein Conformation and Cryptic Pocketsmentioning
confidence: 99%